If the sum of first n terms of an A.P. is cn2, then sum of squares of these n terms is?


ans:n(4n2-1)c2/3


 


HOW?

2 years ago

Share

Answers : (1)

                                        

If a is 1st term and d is common difference, sum of n terms = (n/2) (2a + (n-1)d) = (2an-nd) + n2d


 


comparing this with cn2 we get : 2an-nd = 0  and  d = c    =>    a = c/2,  d = c


 


sum of squares of n terms = \sum_{r=1}^{n}(a+(n-1)d)^{2}


 


=\sum_{r=1}^{n}\left( \frac{c}{2}+(n-1)c\right)^{2}


 


=\sum_{r=1}^{n}c^{2}\left( n^{2}-n+\frac{1}{4}\right)


 


=c^{2}\left( \sum_{r=1}^{n}n^{2}-\sum_{r=1}^{n}n+\sum_{r=1}^{n}\frac{1}{4}\right)


 


=c^{2}\left(\frac{n(n+1)(2n+1)}{6}-\frac{n(n+1)}{2}+\frac{n}{4}\right)


 


=\frac{c^{2}n(4n^{2}-1)}{12}

2 years ago

Post Your Answer

More Questions On Algebra

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
the third term of a geometric progression is 4 product of first five term is?
 
 
Hello Student, Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar one month ago
ax^2+bx+c=0 has real roots a1x^2+b1x+c1=0 has real roots then the roots of (a+a1)x^2+(b+b1)x+c+c1=0
 
 
Ans: may be real or non real.roots Case 1: let ax^2+bx+c=0 be x^2 + 2x + 1 = 0 & a1x^2+b1x+c1=0 be x^2 – 2x + 1 = 0 then (a+a1)x^2+(b+b1)x+c+c1=0 will be x^2 + 2 = 0 which has non real...
 
Y RAJYALAKSHMI 25 days ago
The total no of term free from radical signs in the expansion of (y^{1/5}+x^{1/10})^55
 
 
Hello Student, The general term in the expansion of (y^{1/5}+x^{1/10})^55 is given by =>r/5,r/10 should be integers =>r=0,10,20,30,40,50 =>6 terms Thanks & Regards Arun Kumar...
  img
Arun Kumar one month ago
find the solutions sin2x-12(sinx-cosx)+12=0
 
 
Ans: We need to do hit & trial in this case So the combined solution is This satisfy the original equation.
  img
Jitender Singh one month ago
evaluate ∫ 1 / 1 – cos 2x dx
 
 
Ans: Hello Student, Please find answer to your question below
  img
Jitender Singh 5 days ago
sinx*tanx-1=tanx – sinx find the general solution.
 
 
Hello Student, Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar one month ago
View all Questions »